Innovative endovascular technique for treatment of rare cause of haemoptysis in young. (25th January 2013) - Chadha, Davinder; Handa, Ajay; Chandra, Subash
Abstract : A 17-year-old boy reported for evaluation of two episodes of massive haemoptysis. His clinical examination was unremarkable and investigations (haemogram, coagulogram, serological tests for connective tissue disorders) were normal. A 64-slice CT angiography revealed a saccular aneurysm of 3.8×3.7×3.3 cm arising from the right lower lobe pulmonary artery which was confirmed by cardiac catheterisation. The aneurysm was successfully blocked with a 16–14 Amplatzer duct occluder. A repeat CT angiogram performed after 15 days revealed the device in situ obliterating the aneurysm. Pulmonary artery aneurysm is an extremely rare cause of massive haemoptysis and indicates imminent rupture of the aneurysm which can be rapidly fatal. This case highlights the importance of using an innovative endovascular technique for treatment of a rare cause of haemoptysis.